(untitled) (Journal of Pakistan Orthopaedic Association, 2017)
Objective: To find out the epidemiology and in-hospital clinical outcome of post traumatic major limb amputations. Methods: This descriptive case series study was carried from February 2014 to June 2016. Life saving major limb amputations were performed in Accident and emergency Department (A & E) in patients of both gender and any age fulfilling the inclusion criteria. The demographic data and clinical data of mechanism of injury, level of amputation, associated injuries, Mangled Extremity Severity Score (MESS), postoperative stump wound infection, length of hospital stay and mortality were recorded. Patients were followed up till discharge from hospital. Results: A total of 82 patients(87 major limb amputations) with mean age 29 years (range 7 to 48 years) were enrolled in this study. Male patients were 77(93.9%) while female patients were 5(6%). Motor bike accident was accounted for the highest number of limb amputations (n=21, 24.1%) followed by sugar cane crusher machine (n=13, 14.9%). Upper limb amputations were 59.7% while 40% were of lower limb.Below elbow amputations were 39% while above elbow were 20.6%. Below knee amputations were 29.8% while above knee were 10.3%. Stump wound infection was reported in 16%. Stump refaschioning or revision was done in 28.7%. Five (6%) patients died in hospital. In hospital mortality was 6%. Conclusion: Upper limb amputations were more frequent than lower limb. Below elbow amputations were more common than above elbow or below knee amputations.Younger male patients(15 to 20 years) with motorbike injury was the most commonly affected group.Stump wound infection was the most common post operative complication. Key words: Trauma, Amputation, Mangled Extremity Severity Score(MESS).